“Electrical Characterization of Ruddlesden-Popper Phases with Preferred Orientations and Tunable Composition [La,Sr][Al,Ga,Mg,Na]O4-Δ ″ - Serafini, D; Marino-Velasquez, C (Elsevier Ltd, 2025)
This work investigates the structural, morphological, and electrical properties of a Ruddlesden-Popper phase LaSrAl0.4Ga0.4Mg0.1Na0.1O4-δ, synthesized via the Pechini method, with potential applications as a solid electrolyte in solid oxide fuel cells (SOFCs). For the first time, this phase exhibits a preferred crystallographic orientation and a plate-like microstructure with 45° alignments around the compression axis. X-ray diffraction (XRD) and Rietveld refinement confirm a strong orientation of the (004) and (105) Miller planes and a proper Ga/Al cation distribution at the Wyckoff 2a site. Scanning electron microscopy (SEM) reveals a dense (∼96 %) plate-like microstructure. Electrical characterization demonstrates a significant three-order-of-magnitude improvement in conductivity compared to undoped samples, with values of 28.9 mS/m at 845 °C and 13 mS/m at 749 °C. The oxygen ion activation energy is reduced by 22 % (1.28 eV) due to Mg and Na dopants, which enhance oxygen vacancy formation and ion mobility. Additionally, a distribution of relaxation times (DRT) analysis was performed using DRT Tools software, distinguishing contributions from intergranular conduction (0.2–1.2 μS), grain boundary conduction (3.9–29 μS), and electrode-electrolyte interface processes (78–500 μS) at 507°C-592 °C. These findings highlight the potential of this material for SOFC applications, offering enhanced ionic transport properties and improved densification. © 2025 Elsevier Ltd and Techna Group S.r.l.